Critical Thinking in Slovakia after Socialism - Larson, Jonathan L. (Book collections on Project MUSE., 2013)
Critical thinking is considered the civic virtue of a liberal democracy. Citizens who think for themselves, cooperate, and can agree to disagree are the hallmark of a self-governing society. Citizens of nondemocratic societies, however, are believed to lack this virtue. Authoritarian regimes, it is thought, smother critical discourse through fear and dull critical thought through the control of information and dissemination of propaganda. Since the end of Communist rule in 1989, Western agents of democratization and educational development have criticized the residents of the former Czechoslovakia for this deficiency. In fact, these critics aver that the Slovaks' inability to think critically is the reason the nation has struggled to integrate with Western Europe. Critical Thinking in Slovakia after Socialism interrogates the putative relationship between critical thought and society through an ethnographic study of civic discourse in post-1989 Slovakia. Drawing on original fieldwork as well as on anthropological theories of language and culture, Jonathan Larson uncovers traces of patterned elements of criticism throughout the Slovak political discourse. In addition he exposes ways that these discursive practices have been misinterpreted and overlooked, and outlines unexpected historical and interactive limitations on criticism. This important volume, bringing together scholarship on East Central Europe, liberalism, education, and the public sphere, gives students of modern history, political science, and economics fresh perspective on an essential civic skill. Jonathan L. Larson is Visiting Assistant Professor of Anthropology at the University of Iowa.